2004
DOI: 10.1016/j.febslet.2004.08.031
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic selection and characterization of randomly produced non‐haemolytic mutants of the toxic sea anemone protein sticholysin II

Abstract: A rapid screening method for haemolytic activity, using blood agar plates, has been developed to analyze randomly produced mutant variants of the pore-forming protein sticholysin II (Stn II). Those exhibiting a reduced activity were selected and the DNA corresponding to each Stn II variant sequenced. Once the mutation produced was determined, protein variants were isolated and characterized in terms of structure (circular dichroism spectra and thermal stability) and haemolytic activity. Three single mutation p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 16 publications
1
33
0
Order By: Relevance
“…The importance of tyrosyl side chains for toxin function was shown by Turk et al (66), where chemical modification of tyrosines in EqtII almost completely abolished hemolytic activity. In agreement with our model, in sticholysin II a mutation of the tyrosine equivalent to Tyr 113 (mutant Y111N) largely abolishes hemolytic activity (67). Furthermore, by introducing a 19 F label on EqtII tryptophans, it was shown that Trp 112 is important for SM recognition, as specific NMR chemical shifts were observed upon the addition of SM to PC micelles (31).…”
Section: Discussionsupporting
confidence: 81%
“…The importance of tyrosyl side chains for toxin function was shown by Turk et al (66), where chemical modification of tyrosines in EqtII almost completely abolished hemolytic activity. In agreement with our model, in sticholysin II a mutation of the tyrosine equivalent to Tyr 113 (mutant Y111N) largely abolishes hemolytic activity (67). Furthermore, by introducing a 19 F label on EqtII tryptophans, it was shown that Trp 112 is important for SM recognition, as specific NMR chemical shifts were observed upon the addition of SM to PC micelles (31).…”
Section: Discussionsupporting
confidence: 81%
“…Whereas R29Q and Y111N present a marked decrease in the association constant K, F106L showed an affinity constant only ~ 3 times lower than wild-type. Phe-106 is one of the aromatic residues presumably involved in the interaction with the lipid-water interface 16 . In fact, its relative binding and hemolytic activities are coincident ( Table 2), suggesting that the decrease in the hemolytic activity of this mutant may be explained only by a defective lipid binding.…”
Section: Discussionmentioning
confidence: 99%
“…probably establish cation-π interactions 16 . Therefore, Arg-29 seems to be a crucial residue in the mechanism of pore formation, since it may participate in both membrane recognition and conformational changes leading to pore formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding this study, the most important characteristic of EqtII is its remarkable SM specificity. EqtII recognizes SM during membrane binding via a phosphocholine (POC) binding site and an adjacent aromatic amino acid cluster (13,16,18). Because PC and SM possess the same POC headgroup and EqtII binds isolated SM analogues (16), the toxin therefore is sensitive to the characteristic SM chemistry below the headgroup rather than its headgroup or bulk phase behavior.…”
mentioning
confidence: 99%